The vertebrate fauna of the Upper Permian of Niger — II, Preliminary description of a new pareiasaur - Sidor, Christian A.; Blackburn, David C.; Gado, Boube (Bernard Price Institute for Palaeontological Research, 2003)
The skull of a new pareiasaur, Bunostegos akokanensis gen. et sp. nov., is described on the basis of a partial skull from the Upper Permian Moradi Formation of north-central Niger. Autapomorphies of the genus include the presence of three hemispherical bosses at the tip of the snout, an enlarged laterally projecting supraorbital boss positioned on each postfrontal, and additional, smaller bosses on the squamosal and supratemporal bones. Bunostegos is further characterized by a tab-like process of the nasal that articulates with the frontal, a pineal foramen located equidistant between the parietal-frontal and parietal-postparietal sutural contacts, a postparietal that is excluded from the caudal margin of the dorsal skull roof, and a blunt interpterygoid vacuity. The discovery of Bunostegos suggests an unsuspected degree of biogeographic endemism for central West Africa during the Late Permian.
Main article
Keywords: Permian, Moradi Formation, West Africa, Niger, Pareiasauria, Parareptilia.